2008
DOI: 10.1021/ol8004672
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of (+)-Phoslactomycin B

Abstract: (+)-Phoslactomycin B was synthesized by a highly enantio- and stereoselective approach involving asymmetric pentenylation, Suzuki-Miyaura coupling, ring-closing metathesis, asymmetric dihydroxylation, and Stille coupling. The synthetic method developed enables us to synthesize three other isomers concerning the C11-OH and Delta12-double bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…[34][35][36][37] Due to their intriguing molecular architectures and potential as lead compounds for anticancer drugs as well as their importance as a biological tool, this family of compounds has attracted much attention in the chemical and biological research communities. Thus, there have been a number of synthetic studies including formal and total syntheses of phoslactomycin A 38) and B, [39][40][41][42] leustroducsin B, [43][44][45][46][47] fostriecin, [47][48][49] and PD113,271. 50) However, in spite of their similarity, previously reported synthetic methods are not of general utility in preparing all members of this family.…”
Section: Asymmetric Morita-baylis-hillman Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] Due to their intriguing molecular architectures and potential as lead compounds for anticancer drugs as well as their importance as a biological tool, this family of compounds has attracted much attention in the chemical and biological research communities. Thus, there have been a number of synthetic studies including formal and total syntheses of phoslactomycin A 38) and B, [39][40][41][42] leustroducsin B, [43][44][45][46][47] fostriecin, [47][48][49] and PD113,271. 50) However, in spite of their similarity, previously reported synthetic methods are not of general utility in preparing all members of this family.…”
Section: Asymmetric Morita-baylis-hillman Reactionmentioning
confidence: 99%
“…Previously, we demonstrated 41,51,52) that ynones 19 and 20 effectively served as pivotal intermediates for the synthesis of 17 and 18 as well as their various isomers via Z-or Eselective conjugate addition of hydroiodic acid, C9-hydroxydirected anti-or syn-selective reduction of the C11-carbonyl group, Stille coupling, and phosphorylation as major transformations (Chart 7). From the retrosynthetic perspective, we envisioned epoxide 22 as a common precursor of 19 and 20 by the disconnection via ethynylation, ring-closing metathesis, and asymmetric allylation or pentenylation.…”
Section: Asymmetric Morita-baylis-hillman Reactionmentioning
confidence: 99%
“…To circumvent the problem, we decided to switch the order of our synthetic sequence and performed the ruthenium-catalyzed hydrosilylation reaction prior to the RCM step. Thus, dienyne 7 was first hydrosilylated under the conditions developed by Trost and Ball [11] with HSi(OEt) 3 in the presence of [Cp*Ru(MeCN) 3 ]PF 6 (1 mol %), and subjected subsequently to RCM with the second-generation Grubbs catalyst ([Ru]-II; 5 mol %) to afford the corresponding d-lactone. The d-lactone was then treated with AgF to remove the two silyl groups (Table 2, entry 2).…”
Section: Entry 1)mentioning
confidence: 99%
“…[4e] Owing to the very limited natural availability of (À)-pironetin, as well as its interesting mode of action and its unique structure, this natural product has been the focus of considerable synthetic interest, which has resulted in the development of several total syntheses. [5] Herein we report a highly stereoselective and straightforward synthesis of (À)-pironetin (1) for which we developed two novel and efficient synthetic methodologies: a stereoselective boronmediated pentenylation reaction [6] [Scheme 1, Eq. (1)] and a one-pot hydrosilylation/ring-closing metathesis (RCM)/protodesilylation reaction [Scheme 1, Eq.…”
mentioning
confidence: 99%
“…[10] SAR studies showed the importance of the unsaturated lactone. [11] Two total syntheses of leustroducsin B by Fukuyama [12] and by Iminashi [13] as well as two successful routes to phoslactomycin B by Kobayashi [14] and by Hatakeyama [15] have been reported. Cossy has achieved formal total synthesis of leustroducsin B [16] and phoslactomycin B.…”
Section: Introductionmentioning
confidence: 99%